Penerapan Strategi Digital Marketing untuk Meningkatkan Penjualan UMKM Hokkian Soup Ikan - Hesniati, Hesniati; Hartono, Benedicte (Pakis Journal Institute, 2024)
Hokkian Soup Ikan, an SME in Batam, Indonesia, has been serving authentic Hokkien-style fish soup since 2003. Despite its popularity, it faces challenges in digital marketing, such as limited skills, time constraints, and adapting to changing algorithms, which hinder business growth. This community service project addressed these issues by implementing digital marketing strategies, including improving Instagram content, organizing a Linktree page, and optimizing the Google Maps profile. As a result, the business gained 100 new Instagram followers, received more positive reviews on Google Maps, and improved its online presence. These outcomes demonstrate how targeted digital marketing strategies can help SMEs enhance visibility, attract customers, and utilize technology to remain competitive, even with limited resources.